PENGEMBANGAN MEDIA INTERAKTIF BERBASIS SPINNING WHEEL KELAS IV UPTD SDN MOARAH 01 KLAMPIS - Na'miyah, Husniatun; Ika Dian Rahmawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to develop an interactive learning media based on a Spinning wheel for the life cycle of living things material for fourth-grade Elementary school students and to determine the validity level of the developed Media. This study used the Research and Development (R&D) method with the ADDIE development model limited to the development stage. The research stages Included analyze, design, and development. The analyze stage consisted of material Analysis, student characteristics analysis, problem analysis, and learning media Analysis. The design stage included designing the media appearance, preparing Learning materials, question grids, practice questions, and validation instruments. The development stage was carried out by realizing the design into a spinning Wheel-based interactive media product and conducting validation by material Experts, media experts, and presentation experts. The validation results showed that The media obtained a percentage of 92.72% from material experts with a very valid Category, 93.33% from media experts with a very valid category, and 100% from Presentation experts with a very valid category. Based on these results, the spinning Wheel-based interactive media was declared valid and feasible to be used as a Learning media for science and social studies (IPAS) on the life cycle of living things Material for fourth-grade elementary school students.